Perspectives on Directors' Transformational Leadership: Insights from Cambodian High School Teachers - Em, Sereyrath; Mok, Sarom; Sam, Rany (Journal of General Education and Humanities, 2024)
Different types of leaders work in various settings. School directors have always been regarded as essential individuals in school settings, and they are usually regarded as sample individuals for teachers and other educational staff. The current study investigates high school teachers' perceptions of directors' transformational leadership (DTL) in four Cambodian provinces, concentrating on five essential dimensions: idealized influence (attributes), idealized influence (behaviours), inspirational motivation, individual consideration, and intellectual stimulation. Six hundred thirty-nine teachers participated in the study, indicating favourable evaluations of their directors' leadership methods. Although most variables exhibited uniform perceptions, the findings revealed significant differences in inspiring motivation and individual consideration, especially amongst Kampong Cham and Kampong Chhnang teachers. Teachers in Kampong Cham indicated elevated perceptions of motivation and personalized support from their directors, implying that the efficacy of leadership may differ by provincial settings. These findings emphasize the significance of comprehending local dynamics in educational leadership and reinforce the essential function of DTL in cultivating a supportive and motivated atmosphere for teachers. The study underscores the necessity for customized leadership approaches to elevate teacher satisfaction and promote educational findings in Cambodian schools. Last, but not least, it is recommended that future studies be conducted in provinces other than the four that were part of the current study and that the number of participants is increased. Additionally, combination designs and qualitative designs are recommended.